Clogging susceptibility of a drip irrigation system designed for family farming - Deus, Fábio Ponciano de; Ferrarezi, Rhuanito Soranz; Primo, Renan; Martins, Guilherme Alonso; Testezlaf, Roberto (Coffee Science - ISSN 1984-3909, 2015)
Family farming is an important part of the agribusiness, accounting for a significant part of food production system that supplies the Brazilian domestic market. Irrigation equipment manufacturers have developed alternative technologies for family farming, as the KIFNET™ drip irrigation system, which uses only gravity to pressurize the emitters. The aim of this study was to evaluate the temporal variability of the hydraulic characteristics of a drip irrigation system for family farming, installed in accordance with manufacturer’s guidelines for coffee plants, and infer emitter clogging susceptibility. The evaluation was performed in the initial phase of plant growth during the dry season. New emitters were hydraulically evaluated using tap water, with the determination of the characteristic curve for five pressure values. We also evaluated the clogging susceptibility of the equipment (clogging degree, CD) when installed in the field and using water with suspended solids. In the evaluation with tap water, new emitters showed a coefficient of variation of 2.16 %, Christiansen’s uniformity coefficient (CUC) of 98.01%, and distribution uniformity (DU) of 96.84%. In the field evaluation, with the system operating according to the manufacturer guidelines, the uniformity coefficients have reached lower values than the tests with tap water (CUC=90.30% and DU=85.79%), because of the equipment layout in the field – as the area had a slope of 10% – and by the emitters clogging (CD=6.79%) after 24 irrigation events. The system uniformity and the manufacturing quality were classified as good according to the ASABE standard for drip irrigation, with average clogging degree within the acceptable range for the assessment time, showing technical feasibility for application of this system in family farming if used properly and with preventive maintenance.